Recipes for love and murder - Andrew, Sally (Andrew, Sally. Tannie Maria mystery., 2015)
Meet Tannie Maria: a woman who likes to cook a lot and write a little. One Sunday morning, as Maria savours the breeze through the kitchen window whilst making apricot jam, she hears the screech and bump that announces the arrival of her good friend and editor, Harriet. What Maria doesn't realise is that Harriet is about to deliver the first ingredient in two new recipes (recipes for love and murder) and a whole basketful of challenges.